The effectiveness of the implementation methods of forming a psychophysical readiness for future law enforcement officers to work in conditions of risk - Bondarenko Valentin Vladimirovich (Kharkov National Pedagogical University, 2011)
Theoretically justified method of forming psychophysical readiness for future law enforcement officers to work in a collision with the offender, armed with knives. The experiment involved 62 students. The positive dynamics of the theoretical and practical training of cadets. It is established that the main causes of the clashes with the enemy with negative consequences is the appearance of carelessness, lack of concentration and lack of development of speed. Accentuated the lack of theoretical proficiency that will not allow early detection of aggressive intent in the actions of the enemy and the appropriate response.